Spiritual Modernisation of Student Youth - Zhetpisbayeva, B.A.; Zhilbayev, Zh.O.; Syrymbetova, L.S.; Dyakov, D.V.; Muratova, L.M. (Journal of Siberian Federal University. Humanities & Social Sciences, 2020)
The article is devoted to the problem of implementing the national programme for the spiritual revival of Kazakhstani society. Based on empirical data, the authors of the article analyse the degree to which students develop spiritual values of the programme and substantiate the role of the pedagogical community in developing mechanisms for its implementation. The authors conclude that most students are aware of the provisions of the programme, but have not made them part of their system of values, life goals, and attitudes. In the context of this, the authors offer their own conceptual approach to the issue of implementing the programme in the conditions of Kazakhstani universities.
Keywords: spiritual revival of society; modernisation of consciousness; values; social portrait; students; academic community; Kazakhstan; Kazakhstani; the concept of promoting values